Regulatory fit and preference reversal - Roy, Rajat (School of Marketing, Curtin Business School, 2008)
This research examines how regulatory fit affects the evaluation of hedonic and utilitarian attributes of products. The results show that promotion- focused people has higher evaluation of hedonic attributes over utilitarian attributes. The reverse is true for prevention focused subjects. In addition the authors also find that "evaluation mode" moderates the effect of regulatory fit on product evaluation. Specifically, we present evidence that the above effect holds in a single mode of evaluation (SE) but not in a joint mode of evaluation (JE). In the joint mode of evaluation, subjects prefer the hedonic attributes irrespective of their regulatory focus conditions.